A Project feasibility study on Fibe2O Fiberwater - Boyonas, Mark Ismael (College of Engineering, 2002)
In recent years one of the fastest growing industries in the Philippines is the food beverage industry. A positive growth rate has always been observed in recent years and an ever increasing demand for food beverage products that satisfy specific needs also exists. Thereby, creating an opportunity for new beverage products to capture a share of the demand of the market. The product that is studied is called Fibe₂O Fiberwater. The name was chosen due to its easy recall and its suggestiveness of the nature and purpose of the product, and that is to provide dietary fiber supplement together with bottled water. The product targets a specific segment of the market that needs fiber supplementation without the need of increasing the intake of vegetable and other fiber-rich food. The market study has established an increasing level of demand for the product following the industry-wide growth rate for beverages. The distribution will follow an increasing level of geographic dispersion, starting from Metro Manila slowly expanding to include regional urban centers. The promotion of the product will entail the use of several methods such as product samplings, promotional posters, a launching activity and others. The marketing and promotions budget totals to P6,633,476.5 for the 5 year planning horizon. The manufacturing plant will be located in LISP I in Cabuyao, Laguna, covering an area of 1500 sq. meters. The plant will house the production area, the administrative offices as well as the necessary storage area that will be needed for raw material and finished goods. Suppliers for production equipment has been selected to optimize the efficiency and the expansion capabilities of the production plant. A total investment of P30,869,294.00 for fixed investments is estimated. This covers production equipment, material handling equipment, and building construction as well as land. A total project cost of P57,302,001.03 is allocated in order for production to commerce. This includes venture initiation costs as well as working capital and some contingency allocations. The product will be manufactured under the management of Water Innovations Inc. which is a corporation that will be raising equity for P 20,000,000 from private investors. The remaining P40,000,000 needed to complete the total project cost will be raised through borrowing from the Philippine National Bank. The project has been evaluated financially to be sound enough to generate the right amount of cash that will ensure its safe and continuous operations. The project will be able to generate more than enough amount of money that will allow it to pay off its obligations in less than a year. The project has been shown to be attractive enough to generate a rate of return of 55% which is way greater than the minimum attractive rate set at 30%. The project is deemed to be sound enough to be called feasible and worthy enough to be invested upon. In addition to potentially earning a lot, the project will generate jobs that will benefit the economy. Expenditures on local suppliers will stimulate the economy. This means that over-all the project will yield a potential benefit to investors as well as the society.